Effect of Combined Feedback and Verbal Encouragement on Anaerobic Performance, Technical and Physiological Aspects During Small-Sided Basketball Games for Students’ Girls - Mekni, Rim; Hammami, Mohamed Ali; Sahli, Faten; Selmi, Okba; Stanica, Gabriel; Panaet, Adelina Elena; Alexe, Cristina Ioana; Trabelsi, Omar; Ben Ezzeddine, Lamia (International Journal of Sport Studies for Health, 2024)
Objective: The aim of this research is to determine the effect of combined feedback and verbal encouragement on anaerobic performance, technical and physiological aspects during small-sided Basketball games for adolescent schoolgirls.Material and Methods: Sixty schoolgirls were divided into 3 groups of 20 girls: control group (G1) (mean ± standard deviation (M±SD); age:15.45 ± 0.41years), verbal encouragement group (G2) (M±SD; age:15.65 ± 0.61years) and combined feedback and verbal encouragement group (G3) (M±SD; age:15.55 ± 0.51 years). Muscle power (countermovement jump (CMJ); 5-Jump-Test (5JT)), agility (Illinois-test), sprint speed (10 and 30 m)]; technical skill and heart rate (HR) responses during 3 vs. 3 small sided basketball game (SSBG) were measured. Additionally, HR was continuously recorded and video analysis was used to quantify technical actions during SSBG.Results: The results showed greater improvements in muscle power of CMJ and 5JT for G3 compared to G2 (P